PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMAN 19 GARUT - siti Fauziah, Putri; Tutun Usman, Asep; Munawaroh, Nenden; Masripah (AL MURABBI, 2025)
This study examines the effect of differentiated instruction on students’ learning motivation in Islamic Religious Education (PAI) at SMAN 19 Garut. The empirical gap identified is the lack of diverse teaching methods in PAI, which affects student engagement and motivation, especially in understanding abstract concepts. This study aims to analyze the impact of differentiated instruction by adjusting teaching strategies based on students’ readiness, interests, and learning styles. A quantitative descriptive method with simple linear regression was applied, collecting data through a Likert-scale questionnaire with high validity and reliability (Cronbach’s Alpha: 0.945 for differentiated instruction and 0.941 for motivation). The findings indicate a significant positive effect, with a regression coefficient of 0.633 (p < 0.001) and an R² value of 35.8%, demonstrating that this method substantially enhances students’ intrinsic and extrinsic motivation. This research contributes practical insights for educators to implement adaptive teaching strategies, particularly in abstract subjects like PAI, through group discussions, project-based learning, and multimedia integration. The study also supports the Merdeka Curriculum framework in fostering more engaging and student-centered learning environments